Description of a new species of Euglossa (Hymenoptera: Apidae: Euglossini) with notes on comparative biology - Rasmussen, Claus; Skov, Charlotte (Zootaxa, 2006)
Here, we descr ibe Euglossa rufipes Rasmusse n & Skov sp. nov. from r emnants of Andean rainforest in western Peru and Ecuado r. The species closely resemble s E. asarophora Moure & Sakagami, bu t ma les can be distingui shed by the red color of the h ind tibia an d by geni tal characters. We summarize th e kno wn biological information for both species.